Mesenchymal Stem Cells as Feeder Cells for Pancreatic Islet Transplants (The Review of Diabetic Studies, 2023)
Allogeneic islet transplant serves as a source for insulinsecreting beta-cells for the maintenance of normal glucose levels and treatment of diabetes. However, limited availability of islets, high rates of islet graft failure, and the need for life-long non-specific immunosuppressive therapy are major obstacles to the widespread application of this therapeutic approach. To overcome these problems, pancreatic islet transplantation was recently suggested as a potential target of the “therapeutic plasticity” of adult stem cells. In fact, new results suggest that stem/precursor cells, and mesenchymal stem cells in particular, co-transplanted with islets can promote tissue engraftment and beta-cell survival via bystander mechanisms, mainly exerted by creating a milieu of cytoprotective and immunomodulatory molecules. This evidence consistently challenges the limited view that stem/precursor cells work exclusively through beta-cell replacement in diabetes therapy. It proposes that stem cells also act as “feeder” cells for islets, and supporter of graft protection, tissue revascularization, and immune acceptance. This article reviews the experience of using stem cell co-transplantation as strategy to improve islet transplantation. It highlights that comprehension of the mechanisms involved will help to identify new molecular targets and promote development of new pharmacological strategies to treat type 1 and type 2 diabetes patients.